Human islets and dendritic cells generate post-translationally modified islet autoantigens. (17th May 2016) - McLaughlin, R J; de Haan, A; Zaldumbide, A; de Koning, E J; de Ru, A H; van Veelen, P A; van Lummel, M; Roep, B O
Summary: The initiation of type 1 diabetes (T1D) requires a break in peripheral tolerance. New insights into neoepitope formation indicate that post-translational modification of islet autoantigens, for example via deamidation, may be an important component of disease initiation or exacerbation. Indeed, deamidation of islet autoantigens increases their binding affinity to the T1D highest-risk human leucocyte antigen (HLA) haplotypes HLA-DR3/DQ2 and -DR4/DQ8, increasing the chance that T cells reactive to deamidated autoantigens can be activated upon T cell receptor ligation. Here we investigated human pancreatic islets and inflammatory and tolerogenic human dendritic cells (DC and tolDC) as potential sources of deamidated islet autoantigens and examined whether deamidation is altered in an inflammatory environment. Islets, DC and tolDC contained tissue transglutaminase, the key enzyme responsible for peptide deamidation, and enzyme activity increased following an inflammatory insult. Islets treated with inflammatory cytokines were found to contain deamidated insulin C-peptide. DC, heterozygous for the T1D highest-risk DQ2/8, pulsed with native islet autoantigens could present naturally processed deamidated neoepitopes. HLA-DQ2 or -DQ8 homozygous DC did not present deamidated islet peptides. This study identifies both human islets and DC as sources of deamidated islet autoantigens and implicates inflammatory activation of tissue transglutaminase as a potential mechanism for islet and DC deamidation.